2021
DOI: 10.1109/emr.2021.3050406
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Service Operations for Survivals of SMEs Under COVID-19: Two Cases in Hong Kong

Abstract: The COVID-19 pandemic creates an unseen challenge to the world's business operations. In order to survive, companies have taken all kinds of measures. However, for SMEs, owing to relatively limited resources, surviving COVID-19 requires innovative measures. In this paper, we examine two interesting "innovative solutions" which are practiced in Hong Kong as operational strategies to deal with COVID-19. Managerial implications are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…En el sector de la moda se empezó a utilizar el servicio de WhatsApp por las tiendas físicas individuales y miembros de su personal. En el sitio web de la empresa, se puede ver una lista de tiendas que brindan números de WhatsApp, los consumidores pueden comunicarse con los vendedores en la tienda en la que desean comprar a través de WhatsApp, los pedidos se pueden realizar con la ayuda de los vendedores y así organizar las entregas (Caballero-Morales, 2021, Choi y Sethi, 2021.…”
Section: Adaptarse O Adaptarse: El Surgimiento De Nuevos Modelos De N...unclassified
“…En el sector de la moda se empezó a utilizar el servicio de WhatsApp por las tiendas físicas individuales y miembros de su personal. En el sitio web de la empresa, se puede ver una lista de tiendas que brindan números de WhatsApp, los consumidores pueden comunicarse con los vendedores en la tienda en la que desean comprar a través de WhatsApp, los pedidos se pueden realizar con la ayuda de los vendedores y así organizar las entregas (Caballero-Morales, 2021, Choi y Sethi, 2021.…”
Section: Adaptarse O Adaptarse: El Surgimiento De Nuevos Modelos De N...unclassified
“…Choi and Sethi ( 2021 ) examined the innovative business measures to combat the COVID-19 in China. The researchers concluded that the quarantine restrictions led to new innovative operations in business using simple technologies such as WhatsApp technology for service delivery (catering, clothing, leisure) and education (delivery of knowledge to a student outside the traditional classroom, improving organizational issues in education).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under the COVID-19 outbreak, these efforts have become a part of daily life. The COVID-19 pandemic, unlike previous endogenous economic crises, has not just hit the world economy, but introduced new rules and behavior patterns for the population which will remain unchanged after the crisis (Choi & Sethi, 2021 ). The enterprises involved in the manufacturing of physical products, especially labor-intensive industries, have been forced to optimize their business processes, minimize operations or temporarily close their business (Akhmetzhanov et al, 2019 ; Seetharaman, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pandemic situation, the majority of retailers are transforming their business model to demand-specific (Choi and Sethi, 2021). For survival, retailers are engaged in selling 'essential items' and adopted a pull-based strategy and hence the RSCs are switching to new forms of innovation (Sharma et al, 2021a).…”
Section: Retail Supply Chainsmentioning
confidence: 99%